Thermally‐Induced Isomerization of Prenucleation Clusters During the Prenucleation Stage of CdTe Quantum Dots - Wang, Tinghui; Wang, Zhe; Wang, Shanling; Chen, Xiaoqin; Luan, Chaoran; Yu, Kui (Angewandte Chemie International Edition, 2023)
The evolution of prenucleation clusters in the prenucleation stage of colloidal semiconductor quantum dots (QDs) has remained unexplored. With CdTe as a model system, we show that substances form and isomerize prior to the nucleation and growth of QDs. Called precursor compounds (PCs), the prenucleation clusters are relatively optically transparent and can transform to absorbing magic‐size clusters (MSCs). When a prenucleation‐stage sample at 25, 45, or 80 °C is dispersed in a mixture of cyclohexane (CH) and octylamine (OTA) at room temperature, either MSC‐371, MSC‐417, or MSC‐448 evolves with absorption peaking at 371, 417, or 448 nm, respectively. We propose that PC‐371 forms at 25 °C, and isomerizes to PC‐417 at 45 °C and to PC‐448 at 80 °C. The PCs and MSCs are quasi isomers. Relatively large and small amounts of OTA favor PC‐371 and PC‐448 in dispersion, respectively. The present findings suggest the existence of PC‐to‐PC isomerization in the QD prenucleation stage. In the prenucleation stage of colloidal semiconductor CdTe quantum dots (QDs), precursor compounds (PCs) of magic‐size clusters (MSCs) form and isomerize. When the reaction temperature is increased, PC‐371 forms at 25 °C and isomerizes to PC‐448 at 80 °C via PC‐417 at 45 °C. When a prenucleation‐stage sample is placed in a mixture of cyclohexane (CH) and octylamine (OTA), the PCs that have formed transform quickly to their counterpart MSCs.